A new fossil Adamussium (Bivalvia: Pectinidae) from Antarctica - Quaglio, Fernanda; Whittle, Rowan Jane; Gazdzicki, Andrzej; Simoes, Marcello Guimaraes [UNESP] (Polish Acad Sciences Committee Polar Research, 2010)
Adamussium Jonkersi sp nov is described from the Late Oligocene Destruction Bay Formation Wrona Buttress area King George Island (South Shetlands) West Antarctica The unit characterized by volcanic sandstone is a shallow marine( succession deposited in a moderate- to high-energy environment The thin shelled pectinids collected from the lower part of the unit are preserved mostly as complete valves Shell thickness sculpture pattern and umbonal angle suggest a free-living inactive swimming life habit
Keywords: Antarctica; Adamussium; Pectinidae; Destruction Bay Formation; Oligocene